Analyse And Overview on Digital Image Tampering Detection Using Matlab - Manikantan, K (International Journal of Computer Sciences and Engineering, 2025)
Modern digital technology and the availability of increasingly powerful image processing tools can easily manipulate the digital images without leaving obvious visual traces of having been tampered, so there is an urgent need to identify the authenticity of images. In the fields such as forensics, medical imaging, e-commerce, and industrial photography, authenticity and integrity of digital images is essential. In this paper going to see about different types of detection techniques are namely called as active methods, passive, cloning and splicing